Bacillus Sp. as Potential Probiotics for Use in Tilapia Fish Farming Aquaculture – A Review - Vijayaram, Srirengaraj; Chou, Chi-Chung; Razafindralambo, Hary; Ghafarifarsani, Hamed; Divsalar, Elahe; Doan, Hien Van (Annals of animal science, 2024)
Aquaculture is a crucial and rapidly expanding industry in global food production. Fisheries are also an essential socio-economic activity, providing abundant resources and remarkable prospects. However, due to the deteriorating ecological environment, aquatic animals are often exposed to traumatic conditions and are susceptible to bacterial infections that pose significant challenges for aquaculture production. The indiscriminate use of antibiotics in the past has led to the emergence of multidrug-resistant pathogens and sudden outbreaks of infectious diseases, resulting in serious economic losses. Moreover, the use of expensive chemotherapeutic drugs and antibiotics has negative impacts on aquatic environments. Therefore, it is increasingly important to adopt alternative natural agents, such as probiotics and their metabolites, to enhance healthy fish production. Probiotics are microorganisms that have numerous beneficial effects on their hosts. They are environmentally friendly, non-toxic, and cost-effective. This review specifically focuses on the use of sp. as probiotics to promote healthy tilapia production in the aquatic sector, while also examining their interactions with the immune system and gut micro-biota. The information presented in this review can guide future research and promote effective and healthy tilapia culture production.